Tawuran Pelajar: Solidarity in the Student Group and its Influence on Brawl Behaviour - Malihah, Elly; Maftuh, Bunyamin; Amalia, Rizki (KOMUNITAS: International Journal of Indonesian Society and Culture, 2014)
This research is motivated by the reality of the student brawls as a result of increasing solidarity within the students group. This problem emerges as a challenging issue for our education. This study aims to find an answer to the question of how solidarity within student groups in influencing the brawl behavior. The study used a qualitative approach and case study method. Data was collected through interviews, observation, documentary studies, and literature. The findings of the study are: (1) the brawl between students is triggered by hostility, disputes, or conflicts among student groups. (2) The recruitment process of a student groups is natural and based on the proximity of their house location or place of residence, mutual interests, as well as their hang out place. (3) The process of solidarity formation among group members begins with the casual interaction, carrying out activities together, and establishing the feeling of unity. (4) This established group solidarity leads the students to conduct the brawls when their group is under the threat from the other groups. The students will also do the brawls when there are conflicts among students groups and they fail to fulfill their developmental needs as a teenager.Penelitian ini dilatarbelakangi oleh realitas maraknya tawuran dikalangan pelajar sebagai dampak dari meningkatnya solidaritas dalam kelompok. Masalah tersebut menjadi tantangan dunia pendidikan. Penelitian ini ingin memperoleh jawaban atas pertanyaan bagaimana solidaritas pada kelompok pelajar dalam mempengaruhi perilaku tawuran. Penelitian ini menggunakan pendekatan kualitatif dan metode studi kasus. Teknik pengumpulan data dilakukan melalui wawancara, observasi, studi dokumentasi, dan studi literatur. Temuan penelitian: (1) Tawuran antar pelajar yang terjadi dikarenakan perumusuhan, pertikaian atau konflik yang ada diantara kelompok-kelompok pelajar. (2) Proses pelajar menjadi anggota kelompok bersifat alamiah dan didasari karena kedekatan letak rumah atau tempat tinggal, minat yang sama, serta satu tempat tongkrongan. (3) Proses pembentukan solidaritas dimulai dari interaksi diantara sesama anggota kelompok, kegiatan yang dilakukan bersama-sama hingga akhirnya keterlibatan perasaan. (4) Solidaritas yang terbentuk menyebabkan tawuran antar pelajar selama ada ancaman dari kelompok lain, terjadinya konflik diantara kelompok-kelompok pelajar, serta tidak terpenuhinya kebutuhan-kebutuhan perkembangan pelajar sebagai remaja.